2014
DOI: 10.1098/rsbl.2013.1021
|View full text |Cite
|
Sign up to set email alerts
|

Ubxpromotes corbicular development inApis mellifera

Abstract: The key morphological feature that distinguishes corbiculate bees from other members of the Apidae family is the presence of the corbicula (pollen basket) on the tibial segment of hind legs. Here, we show that in the honeybee (Apis mellifera), the depletion of the gene Ultrabithorax (Ubx) by RNAi transforms the corbicula from a smooth, bristle-free concave structure to one covered with bristles. This is accompanied by a reduction of the pollen press, which is located on the basitarsus and used for packing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
(25 reference statements)
1
15
0
1
Order By: Relevance
“…Bomtorin et al (2012) showed that the development of the Bshaved tibia^used by workers to carry pollen (pollen basket) depends upon ultrabithorax expression during prepupal and early pupal phases. This finding was then confirmed by Medved et al (2014) using gene expression interference by RNAi.…”
Section: Honeybee Diphenism and Caste Differentiationsupporting
confidence: 58%
“…Bomtorin et al (2012) showed that the development of the Bshaved tibia^used by workers to carry pollen (pollen basket) depends upon ultrabithorax expression during prepupal and early pupal phases. This finding was then confirmed by Medved et al (2014) using gene expression interference by RNAi.…”
Section: Honeybee Diphenism and Caste Differentiationsupporting
confidence: 58%
“…Shifts in Scr expression influence male sex comb morphology in Drosophila forelimbs (67) and the formation of crustacean maxillipeds (68). Similarly, regional upregulation of Ubx along insect hindlimbs drives growth and setal loss (69,70), such as that observed in the expanded corbicula pollen basket in honey bees and bumble bees (71). Such variation during late development could be driven by Hox genes evolving to respond to downstream components of regulatory networks, further enabling developmental micromanagement (57,67).…”
Section: P15mentioning
confidence: 99%
“…This is a rare example in which the genomic locus of phenotypic evolution has been identifi ed. In honeybees, workers and queens differ in leg bristle patterns, which are controlled by differences in the timing and expression levels of Ubx (Bomtorin et al 2012 ;Medved et al 2014 ). These caste differences are phenotypically plastic, but it is not yet known how the environmental signal is translated into a difference in Ubx expression.…”
Section: Hox Genes As Micromanagers Of Appendage Morphologymentioning
confidence: 99%